Corrosion of Orthodontic Metallic Brackets Immersed in Solutions of Salt and Spices in Artificial Saliva - Nurul Afiqah Amani Binti Zaaba1, Harish Babu2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Orthodontic treatment is commonly use to treat dental malalignment, especially orthodontic braces as it help to realigned teeth to the normal position as well as for aesthetic purpose. As orthodontic braces is a choice of orthodontic treatment various kind of orthodontic braces had been invented based on the material used, adhesives systems as well as their strengths to bring about tooth movement. As it is placed in the oral cavity, the aggressive environments of the oral cavity, will lead to corrosion of the orthodontic brackets. This may affect it physical properties and clinical performance.Aim: To study the corrosion of orthodontic brackets that immersed in the solution of artificial saliva and spices.Materials and Method: Stainless steel orthodontic brackets were used for this studies. Each bracket was placed in the container contain artificial saliva and other agents. Several types of aqueous solutions were prepared for this study by using different agents (spices). They were pure artificial saliva, salt (sodium chloride), black pepper, turmeric and mixture of all of the spices along with salt. After 24 hours, surface changes was seen under the optical microscope.Results: Based on the study, orthodontic brackets surface immersed in the controlled medium, revealed that more corrosion was seen in the salt medium when compared to pure artificial saliva. More pitting also was seen in the salt medium of the controlled group. Based on the surface analysis of the orthodontic brackets in the studied groups, demonstrate that more corrosion and pitting was seen in the aqueous solution of mixture of artificial saliva with salt and spices and less pitting and corrosion was seen in the turmeric solution.Conclusion: Based on the study, the finding suggest that the corrosion behaviour of the orthodontic brackets is influenced by the presence of a salt (NaCl) and other spices. Salt and black pepper are responsible for the corrosion of the orthodontic brackets, while turmeric capable in reduction or slowing the process of corrosion.